Experimental datasets on processed eggshell membrane powder for wound healing - Tamer A.E. Ahmed; Henri-Pierre Suso; Maxwell T. Hincke (Data in Brief, 2019)
Eggshell (ES) and eggshell membrane (ESM) is a significant byproduct of the egg producing industry (Ahmed et al., 2019). Many studies have been undertaken to utilize ES waste for potential value added applications (Cordeiro and Hincke, 2011). Described here are the datasets from our evaluation of processed eggshell membrane powder (PEP) as a wound healing product using the mouse excisional wound splinting model (Ahmed et al., 2019). PEP biomaterial was characterized by proteomics using various extraction and solubilization strategies including moderate (lithium dodecyl sulphate (LDS) and urea/ammonium bicarbonate) and harsh conditions (3-mercaptopropionic acid (3-MPA) and NaOH/dimethylsulfoxide) in order to progressively overcome its stable, insoluble nature (Ahmed et al., 2019, Ahmed et al., 2017). Analysis of proteomic data allowed the relative abundance of the main PEP protein constituents to be determined. The efficacy of PEP for promotion of wound healing was assessed using the mouse excisional wound splinting model, and well-established semi-quantitative histological scoring. (More details about the PEP biomaterial characterization and its in vivo evaluation can be found in the related research article (Ahmed et al., 2019)). Keywords: Processed eggshell membrane powder, Proteomics, Wound healing, Histological scoring